Performance Analysis of MIMO Antenna Design with High Isolation Techniques for 5 G Wireless Systems - Suverna Sengar; Praveen Kumar Malik; Puneet Chandra Srivastava; Kiran Srivastava; Anita Gehlot (International Journal of Antennas and Propagation)
This paper investigates different approaches for achieving isolation in a MIMO antenna design. It provides an in-depth comparison of these techniques, analyzing their advantages and disadvantages. The challenges of obtaining sufficient isolation in modern MIMO antenna design are discussed, and various isolation methods developed for the MIMO design are examined. The study introduces a compact 28 GHz 4-port MIMO antenna design, which is placed on a Rogers RT/Duroid 5880 substrate. The design includes a rectangular patch with semicircles at the ends and dual slots etched from it. A partial ground plane is integrated into the antenna to achieve an operating frequency range from 22 to 29 GHz, centered at 24 GHz. To reduce mutual coupling between elements, four elements are arranged orthogonally and four stubs are added at a specific frequency band to enhance isolation. The ground plane also incorporates a defected ground structure (DGS) to improve gain. To optimize the antenna’s bandwidth, a ground cut technique is used, resulting in a 0.7 GHz bandwidth enhancement at the cost of some isolation. The antenna operates in the range of 22.5– 29.1 GHz, with a peak gain of 6.39 dBi. Each technique is compared based on parameters such as S-parameters (return loss or reflection coefficient), voltage standing wave ratio (VSWR), isolation level, and peak gain. Simulated results are shown for each of the techniques to compare their performance by using Ansys HFSS simulations which confirm that the designed antenna meets the target band requirements and could be used in 5 G communications.